The Heart-Placenta Axis in the First Month of Pregnancy: Induction and Prevention of Cardiovascular Birth Defects - Kersti K. Linask (Hindawi Limited, 2013)
Extrapolating from animal studies to human pregnancy, our studies showed that folate (FA) deficiency as well as one-time exposure to environmental factors in the first two to three weeks of human gestation can result in severe congenital heart defects (CHDs). Considering that approximately 49% of pregnancies are unplanned, this period of pregnancy can be considered high-risk for cardiac, as well as for neural, birth defects, as the woman usually is not aware of her pregnancy and may not yet be taking precautionary actions to protect the developing embryo. Using avian and mouse vertebrate models, we demonstrated that FA supplementation prevents CHD induced by alcohol, lithium, or elevation of the metabolite homocysteine, a marker for FA deficiency. All three factors affected the important Wnt signaling pathway by suppressing Wnt-mediated gene expression in the heart fields, resulting in a delay of cardiomyocyte migration, cardiomyogenesis, and CHD. Optimal protection of cardiogenesis was observed to occur with FA supplementation provided upon morning after conception and at higher doses than the presently available in prenatal vitamin supplementation. Our studies demonstrate pathways and cell processes that are involved with protection of one-carbon metabolism during heart development.